Inspection Measurement Test Model Design Patrol Boats - , Nandiko.Rizal (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
Measurement is a process or an activity to determine a numerical quantity of an object with the purpose to find the best numerical value of its certain characteristics. The main points of measurement activities are: the purpose of the measurement, object of the measurement, the tools used and the process of how to do the measurement. The result of the measurement is only the estimation of the real values. Measurement, in general, means an activity using a certain chosen principle which could be qualified in some different ways. The procedure of measurement uses a selected method and usually written on a document called “the procedure of measurement” or “the method of measurement” which is written in detail to help the operator works without any further information. This paper will discuss about checking, measuring, and determining the deviation existed on the design process of making the ship patrol model,starting from the preparation until the test it self. The investigated model is characteristically spesific for test and hopefully could be used as the standard of the best optimum model to get as accurate design result as the real ship.